PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI, INTEGRITAS, AKUNTANBILITAS, KOMPETENSI DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT - Rizky Jayanti, 13.05.52.0186; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
This study aims to test and analyze empirically about the influence of auditor experience, independence, integrity, accountability, competence and auditor ethics on audit quality at auditors KAP Semarang, Solo and Yogyakarta. The population used in this study are all auditors KAP Semarang, Solo and Yogyakarta. The sampling method used is convenience sampling, which is sample selection based on convenience, so the author has the freedom to choose the most rapid and easy sample. In this study, the dependent variable used is audit quality, while the independent variables consist of auditor experience, independence, integrity, accountability, competence and auditor ethics. Data analysis technique using multiple linear regression analysis. The results show that the experience of auditors has a positive influence on the quality of auditors. Independence has a positive influence on audit quality. Integrity has a positive influence on audit quality. Accountability has a positive effect on audit quality. Competence has a positive effect on audit quality. The ethical auditor has a positive influence on audit quality.Keywords: Independence, Integrity, Professionalism, Competence, Objectivity, Ethical Compliance and Audit Quality